A Study of Hypoalbuminemia and Pleural Effusionin Pediatric Nephrotic Syndrome - Tovan Perinandika; Dedi Rachmadi; Fenny Dwiyatnaningrum (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Nephrotic syndrome (NS) is a kidney disease that is most often found in children. Hypoalbuminemia in NS can cause a decrease in oncotic pressure causing extravasation of fluid into the interstitial space. In conditions of severe hypoalbuminemia, fluid extravasation may cause occurrence of pleural effusion. The objectives of this study was to analyze the correlation between hypoalbuminemia and pleural effusion in children with NS. Methods: An analytical study was conducted on 69 medical records of pediatric nephrotic syndrome from 1 January 2008–31 December 2013 in dr. Hasan Sadikin General Hospital. Inclusion criteria were pediatric patients between 1-14 years old with NS. Exclusion criteria were patients who already had albumin transfusion, malnutrition, patients with chronic disease, and incomplete medical record information. Contingency coefficient test was carried out to discover the correlation between variables. Results: Out of 89 samples, 69 samples were included. Characteristics of the included patients are male (n=48), female (n=21), age 1–5 (n=24), 6–10 (n=22), 11–14 (n=23), mild hypoalbuminemia (n=3), moderate hypoalbuminemia (n=27), severe hypoalbuminemia (n=39), patients with pleural effusion (n=23), and non-pleural effusion (n=46). There was a significant correlation between hypoalbuminemia and pleural effusion with p=0.000 (p<0.05) and moderate correlation (r=0.437). Conclusions: Hypoalbuminemia has correlation with pleural effusion in pediatric nephrotic syndrome.Keywords: Hypoalbuminemia, pediatric nephrotic syndrome, pleural effusionDOI: 10.15850/amj.v4n2.1075